Determination of Coined-Bead Geometry in the V-Bending Process. (19th August 2014) - Phanitwong, Wiriyakorn; Thipprakmas, Sutasn
Abstract : The coined-bead technique is commonly applied in the V-bending process to eliminate the spring-back feature and to achieve the required bending angle. In the present research, which is based on a stress distribution analysis, the effects of a coined-bead geometry in the V-bending process on the increased compressive stress in the bending allowance zone and on the increased reversed bending zone in the leg of the workpiece were observed and characterized. The research also illustrated the variations in spring-back and spring-go characteristics for different coined-bead widths and heights. As the bead width increased, the spring-go decreased, increased, and decreased again for different simulated bead heights and workpiece materials. The research was able to disprove previously suggested theories for coined-beaded V-bending, which suggested that a smaller bead width should be applied to cancel out the spring-back characteristic. In addition, the spring-back characteristic returned when an oversized bead width was applied. Therefore, to achieve the required bending angle, the size of the bead width was optimized both to provide a balance between a favorable stress distribution in the bending zone and reversed bending zone and to reduce the bending load.